Postpartum Reversible Cerebral Vasoconstriction Syndrome Presenting with Radiological Plethora - Sharma, Manisha; Menon, Bindu; Manam, Gayatri (Indian Journal of Radiology and Imaging, 2021)
Reversible cerebral vasoconstriction syndrome (RCVS) is a clinicoradiological syndrome characterized by segmental vasoconstriction of cerebral arteries with resolution in most patients within 1 to 3 months. It has been known to be a benign uniphasic reversible illness but cases of fulminant RCVS with mortality have also been reported. The symptoms can be varied with presentations like transient ischemic attack (TIA), ischemic stroke (IS), intracerebral hemorrhage (ICH), subarachnoid hemorrhage (SAH), and posterior reversible encephalopathy syndrome (PRES). We report a postpartum female with RCVS with radiological features of ICH, SAH, atypical PRES, and atypical clinical presentation as well. RCVS can be frequently missed unless there is a high index of suspicion. Hence clinicians should be aware of the typical and the atypical presentation of RCVS along with the radiological findings with the potential complications. Early suspicion and detection in the emergency help in recovery and reducing morbidity.
Keywords: reversible cerebral vasoconstriction syndrome; postpartum reversible cerebral vasoconstriction syndrome; postpartum cerebral angiopathy; posterior reversible encephalopathy syndrome